Effects of traditional and resisted sprint training in highly trained, female team handball players - Luteberget, L.; Raastad, T.; Seynnes, O.; Spencer, M. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Effects of traditional and resisted sprint training in highly trained, female team handball players Introduction Resisted sprint training (RST) is a method often used to improve acceleration, an important factor for performance in handball. The objective of RST is to elicit a greater neuromuscular activation and to enhance the recruitment of fast twitch fibres. A load of 12-13 % of body mass is suggested as an optimal load (1). Studies report conflicting results regarding the effectiveness of RST. However, the current knowledge suggests that the effect of RST exceeds traditional sprint training (TST) in short sprints (5-10 m). In addition, ultrasound-based data indicate that fascicle length positively correlates with sprint performance (2), but evidence concerning changes in muscle architecture following sprint training is lacking. The aim of this study was to compare the effects of RST versus TST, upon sprint performance, and to determine whether these effects were reflected in muscle architectural measurements. Method: A group of semi-professional female handball players (n=18) was assigned to either RST group (sled towing, with 12.4±0.2 % of body mass) or TST group matched on 10-m sprint performance. The participants completed two sprint sessions per week for 10 weeks. Sessions included 10-m and 20-m sprints, with a total sprint distance of 240- 280 m per session, equal for both groups. Sprint tests (10-m and 30-m), vertical and horizontal jumps, 20-m shuttle run test and muscle architecture were performed pre- and post-training. Results: Beneficial effects were found in 30-m sprint for both groups (TST=-0.31±0.19 s, RST=-0.16±0.13 s; mean±90% CL), with a moderate effect size between groups (ES=0.85). Only TST had a beneficial effect on 10-m time (-0.04±0.04 s, ES=0.51). Pennation angle decreased in both groups, resulting in a small effect on fascicle length (5.3±3.9 %, ES=0.26 and 4.0±2.1 %, ES=0.46 for TST and RST, respectively). Both groups obtained a small effect size for agility performance (TST=0.46 and RST=0.28). Discussion: Sprint training appears to be effective in enhancing short distance (10-30m) sprints in female handball players, and TST appears to be more effective than RST. The load suggested in previous studies as optimal for RST, may not apply for female athletes. The effect on fascicle length is similar for both groups, yet small in magnitude. This possibly suggests a velocity-specific adaptation to sprint training, present in concurrently training athletes. Specific agility training is advisable to have a better effect on agility performance.